Lex Rei Sittae in the Export of Indonesian Shrimp Commodities to Japan - Sugiono Sugiono; Fany Krisdianto (Universitas Muhammadiyah Gresik, 2023)
In the current global era, countries are encouraged to prioritize international trade. Because one of the most important tools and sources of financing in international trade is the foreign exchange reserve for the country itself. Because of the importance of foreign exchange reserves for a country, where foreign exchange reserves always fluctuate, a number of factors can be tested that can affect the position of foreign exchange reserves, namely the amount of export activity. This article was created with the aim of knowing the export potential of fishery products, more precisely the types of shrimp fisheries in Indonesia. Indonesia itself exports shrimp to various countries, one of which is Japan. By using the descriptive method the author tries to explain the importance of agreements in an engagement, especially activities in international buying and selling along with the legal basis regarding international trade activities carried out by the Indonesian state. Then the results of this article study show that exports have a positive and significant effect on foreign exchange reserves for countries that carry out export activities and the importance of agreement clauses in determining which law will be enforced if one of the parties commits a default in order to protect the rights and obligations of the parties, given the activities International trade is prone to acts of abuse of rights and obligations.